Effects of foot rotation positions on knee valgus during single-leg drop landing: Implications for ACL injury risk reduction - Teng, Phillis Soek Po (2022)
Background: Non-contact anterior cruciate ligament (ACL) injuries commonly occur when athletes land in high risk positions such as knee valgus. The position of the foot at landing may influence the transmission of forces from the ankle to the knee. Using an experimental approach to manipulate foot rotation positions, this study aimed to provide new insights on how knee valgus during single-leg landing may be influenced by foot positions. Methods: Eleven male recreational basketball players performed single-leg drop landings from a 30-cm high platform in three foot rotation positions (toe-in, toe-forward and toe-out) at initial contact. A motion capture system and a force plate were used to measure lower extremity kinematics and kinetics. Knee valgus angles at initial contact (KVA) and maximum knee valgus moments (KVM), which were known risk factors associated with ACL injury, were measured. A one-way repeated measures Analysis of Variance was conducted (α = 0.05) to compare among the three foot positions. Results: Foot rotation positions were found to have a significant effect on KVA (p < 0.001, η2 = 0.66) but the difference between conditions (about 1°) was small and not clinically meaningful. There was a significant effect of foot position on KVM (p < 0.001, η2 = 0.55), with increased moment observed in the toe-out position as compared to toe-forward (p = 0.012) or toe-in positions (p = 0.002). Conclusions: When landing with one leg, athletes should avoid extreme toe-out foot rotation positions to minimise undesirable knee valgus loading associated with non-contact ACL injury risks.